2016
DOI: 10.4068/cmj.2016.52.2.112
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anger Expression and Its Indices and Oral Lichen Planus

Abstract: Oral lichen planus (OLP) is a common inflammatory disease with unknown etiology. Depression, stress and anxiety are psychological factors that their influence on the expression of lichen planus by affecting the immune system's function has been confirmed. There is a probable relationship between anger and OLP expression. Therefore, the present study aimed to evaluate the association of "anger" and OLP. In this descriptive study 95 subjects were included in 3 groups. A: patients with oral lichen planus, B: posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Mehdipour et al . used the Anger Expression‐In scale to determine the correlation between anger and OLP, which showed the OLP group (MD = 69.42) reported greater anger than the control group (MD = 59.00, P = 0.005) 38 …”
Section: Resultsmentioning
confidence: 99%
“…Mehdipour et al . used the Anger Expression‐In scale to determine the correlation between anger and OLP, which showed the OLP group (MD = 69.42) reported greater anger than the control group (MD = 59.00, P = 0.005) 38 …”
Section: Resultsmentioning
confidence: 99%
“… [69] While long term effects of these psychological disorders within the general population remains to be seen, it is of note that anger control has been correlated with OLP suppression. [70] Hence, one can include anger assessment in the COVID-19 patients as a part of prospective analysis.…”
Section: Discussion and Consequences Of The Hypothesismentioning
confidence: 99%
“…The SNS activation directly and indirectly releases epinephrine and norepinephrine through adrenal medulla [17]. Several studies have shown a positive and significant relationship between psychogenic stress and OLP [18][19][20][21], while others did not find a meaningful relationship [22,23]. The adrenergic receptors bind to the catecholamines secreted in response to stress, and lead to their effects in various cells of the body.…”
Section: Discussionmentioning
confidence: 99%